1966
DOI: 10.1002/qj.49709239408
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent energy dissipation rates and exchange processes above a non‐homogeneous surface

Abstract: SUMMARYEnergy dissipation rates and the eddy fluxes of sensible heat, momentum, and total kinetic energy have been measured above a non-homogeneous surface. Calculations were made from simultaneous observations of fluctuations in air temperature and the orthogonal components of wind velocity at heights of 16 m and 40 m. In all thermal stratifications, dissipation rates given by the Kolmogoroff structure function are in close agreement with direct measurements of the energy extracted from the mean flow. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1968
1968
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The third term, +D, represents transport due to the vertical divergences of the vertical flux of turbulent kinetic energy and work done by pressure fluctuations. The relative magnitudes and signs of the terms represented in (5) have been investigated by a number of workers (Record and Cramer, 1966;Fichtl and McVehil, 1970;McBean et al, 1971;Wyngaard and CotC, 1971;Garratt, 1972). The results of these studies have not been unanimous or conclusive, primarily due to the difficulty in evaluating #D. The flux divergence contains a third moment and the instrumental di~culties that the measurement of static pressure presents have left pressure transport to guesswork until only recently.…”
Section: The Stressmentioning
confidence: 99%
“…The third term, +D, represents transport due to the vertical divergences of the vertical flux of turbulent kinetic energy and work done by pressure fluctuations. The relative magnitudes and signs of the terms represented in (5) have been investigated by a number of workers (Record and Cramer, 1966;Fichtl and McVehil, 1970;McBean et al, 1971;Wyngaard and CotC, 1971;Garratt, 1972). The results of these studies have not been unanimous or conclusive, primarily due to the difficulty in evaluating #D. The flux divergence contains a third moment and the instrumental di~culties that the measurement of static pressure presents have left pressure transport to guesswork until only recently.…”
Section: The Stressmentioning
confidence: 99%
“…Since Panofsky (1962) indicated that the divergence of turbulent kinetic energy flux was important in the energy budget of the atmospheric boundary layer, direct measurements of this flux have been made by several researchers (e.g., Record and Cramer, 1966;Maitani and Mitsuta, 1967;. Recently, McBean and Elliott (1975) discussed the stability dependence of normalized kinetic energy flux using their observational results as well as those from other studies (Wyngaard and CotC, 1971;Garratt 1972;Banke and Smith, 1973).…”
Section: Introductionmentioning
confidence: 98%
“…(a) Panofsky (1962) and Record & Cramer (1966) reported TKE evolution in the ASL and showed that the divergence of TKE flux was important under steady-state conditions. Busch & Panofsky (1968) in their spectral study of atmospheric turbulence contested the importance of divergence of TKE flux and showed that dissipation compensates shear and buoyancy productions.…”
Section: Introductionmentioning
confidence: 99%